Improved thermostability of an acidic xylanase from Aspergillus sulphureus by combined disulphide bridge introduction and proline residue substitution - Wenhan Yang (Nature Portfolio, 2017)
Abstract As a feed additive, xylanase has been widely applied in the feed of monogastric animals, which contains multiple plant polysaccharides. However, during feed manufacture, the high pelleting temperatures challenge wild-type xylanases. The aim of this study was to improve the thermostability of Aspergillus sulphureus acidic xylanase. According to the predicted protein structure, a series of disulphide bridges and proline substitutions were created in the xylanase by PCR, and the mutants were expressed in Pichia pastoris. Enzyme properties were evaluated following chromatographic purification. All the recombinant enzymes showed optima at pH 3.0 and 50 °C or 55 °C and better resistance to some chemicals except for CuSO4. The specific activity of the xylanase was decreased by introduction of the mutations. Compared to the wild-type enzyme, a combined mutant, T53C-T142C/T46P, with a disulphide bond at 53–142 and a proline substitution at 46, showed a 22-fold increase of half-life at 60 °C. In a 10-L fermentor, the maximal xylanase activity of T53C-T142C/T46P reached 1,684 U/mL. It was suggested that the T53C-T142C/T46P mutant xylanase had excellent thermostability characteristics and could be a prospective additive in feed manufacture.